Are e-learning challenges adequately addressed in Sri Lanka's rural communities? A qualitative study - Thasika, T.; Dilogini, S. (Technological Advances in Science, Medicine and Engineering, 2024)
Purpose This study aims to explore the insights and misconceptions of small and medium enterprises (SMEs) entrepreneurs in Sri Lanka's arts and crafts industry regarding omni- channel marketing technology. By exploring their perspectives, the study seeks to provide suggestions to enhance their understanding and encourage the adoption of effective omni- channel marketing strategies, thereby supporting their contribution to the tourism industry and global market reach. Design/Methodology/Approach: This study employs a qualitative case study method to gain an in-depth understanding of how arts and crafts entrepreneurs in Sri Lanka perceive and understand omni-channel marketing technology. By selecting 10 SMEs in the arts and crafts industry, the researcher conducts in-depth interviews with the entrepreneurs to gather detailed data. The interview transcripts are then coded to develop themes, and the findings are interpreted within the context of the SMEs' omni-channel marketing strategies. This approach provides rich, contextual insights into the specific challenges and understandings of these entrepreneurs regarding omni-channel marketing. Findings: This study reveals several common misunderstandings about omni-channel marketing among arts and crafts entrepreneurs in Sri Lanka. These include the beliefs that omni-channel marketing simply means being on multiple channels, that developing an omni-channel strategy is only possible for large and well-established enterprises, and that all omni-channel marketing tools are high-cost. Additionally, entrepreneurs often think they cannot adopt omni-channel strategies due to the need for advanced technological skills and that personalized customer interactions cannot be replicated by technology. There is also a misconception that measurable return on investment (ROI) cannot be achieved by entrepreneurs through omni-channel marketing and that omni-channel marketing only encompasses sales and marketing activities. Originality/value: This study explores misconceptions about omni-channel marketing among arts and crafts entrepreneurs, vital for their global expansion and industry advancement. By identifying and understanding these misconceptions, the research provides targeted solutions, filling a gap in the literature and offering valuable insights to enhance entrepreneurs' global competitiveness in omni-channel marketing. Practical Implications: Firstly, entrepreneurs must acknowledge the true nature of omni- channel marketing and understand that it emphasizes quality over quantity, focusing on a seamless and integrated approach across all touchpoints from online to offline. Additionally, they should recognize the availability of low-cost or free tools and consider starting with these before gradually increasing investments. Moreover, entrepreneurs should realize that they can effectively utilize omni-channel marketing technology with user-friendly tools such as basic CRM systems and analytics tools. Understanding that omni-channel marketing can enhance personal interactions by providing additional touchpoints and more personalized customer experiences is crucial. Lastly, entrepreneurs should comprehend that measuring ROI is feasible by concentrating on specific key performance indicators (KPIs), allowing for informed decision-making and strategy refinement. These implications offer actionable insights for entrepreneurs to enhance their understanding and implementation of omni-channel marketing strategies.
Keywords: Arts and crafts industry; Entrepreneurs; Misconceptions; Omni-channel marketing; Return on investment (ROI); Sri Lanka